Synthesis and efficiency of cationic chitosan in the physical-chemical treatment of water - Bastiani, Vanessa Rossato de; Wastowski, Arci Dirceu; Tejada, Luma Schervenski; Volpi, Gabriel Baraldi; Grade, Bruna Thais Lauer; Rosa, Genesio Mario da; Golombieski, Jaqueline Ineu (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2024)
Water for human consumption must comply with legal potability standards, involving treatments that often use chemical agents that have impacts on the environment and human health. An alternative is to use organic polymers, such as chitosan, but in some situations, its structure should be modified to improve its applicability. This is achieved by adding reagents such as CHPTAC to make it cationic. This research aimed to create a cationic polysaccharide derived from chitosan using the CHPTAC reagent and apply it in water treatment, varying dosages and pH. The results showed that the synthesized chitosans achieved good efficiency in removing turbidity and color, in which some dosages were more effective. Furthermore, each flocculant performed better in a specific pH range, often in acidic pH. The research highlighted that both cationic and non-cationic chitosan are effective in water treatment, providing a viable alternative to commonly used inorganic coagulants.